Entwicklung einer Methode zur systematischen Erarbeitung von Maßtoleranzen für additive Fertigungsverfahren - Lieneke, Tobias (Rapid Tech 2015)

Systematical determination of dimensional tolerances for additive manufacturing - Lieneke, Tobias (26th Annual International Solid Freeform Fabrication Symposium)

Towards a sustainable and economic selection of part candidates for Additive Manufacturing - Lindemann, C.; Jahnke, U.; Reiher, T.; Koch, R. (Rapid Prototyping Journal)
Purpose – This paper aims to present a methodology to help end-users to find appropriate part candidates for the use of the additive manufacturing (AM) technology. These shall be capable of bringing AM into their businesses. The concept furthermore includes approaches for redesigning current available parts and helps to estimate the economic implications of the use of the technology. Design/methodology/approach – The approach starts to discuss general economic aspects for the successful use of AM. While describing the introduction of new technologies into existing businesses, the importance of an appropriate part selection for AM is pointed out. A methodology for a part selection process is presented, and the different criteria are developed. An approach for a redesign of the selected parts, including the gathering of requirements, is given based on different sample parts. A variation of criteria to include measures for product piracy is highlighted. Findings – The methodology has proven applicability in several research and industry projects in aerospace applications. Independent part selections from experts analyzed within a project of the European Space Agency had a 90 per cent overlap with the results. It allows companies with only basic AM knowledge to start a part screening for applicable AM candidates in their own company with a reasonable effort. Originality/value – The methodology for the redesign process helps to identify the main functions of the products targeted and the relevant environment, so one can benefit from the various advantages that AM has to offer. The selection methodology helps to ask the right questions and to reduce the effort.

Developement of an economic decision support for the application of Additive Manufacturing in aerospace - Deppe, G.; Lindemann, C.; Koch, R. (26th Annual International Solid Freeform Fabrication Symposium)
Additive Manufacturing offers a high potential in aerospace industry due to its freedom of design and the ability to manufacture complex and lightweight parts. The low number of units, high quality standards and fast response time are special challenges that have to be met especially in the Maintenance, Repair and Overhaul sector. Thus, companies have to decide at which point it is economic to apply Additive Manufacturing. However, companies lack experience on this new technology. This is why a tool is required that takes into account the above mentioned crucial points and supports the decision process. The paper analyzes aviation’s characteristics with regard to Additive Manufacturing. The structure of current MRO repair workflows is investigated to identify a feasible application for Additive Manufacturing. Additionally the supply chain will be examined to indicate the benefit which the technology can generate in this highly demanding field. The findings are integrated into a methodology that supports the decision whether to apply Additive Manufacturing on the basis of costs, time and quality.

Protection measures against product piracy and application by the use of AM - Jahnke, U.; Büsching, J.; Reiher, T.; Koch, R. (26th Annual International Solid Freeform Fabrication Symposium)
Presently the implications Additive Manufacturing (AM) on intellectual properties are discussed in public. Here AM is often mentioned as a driver for product piracy as it allows to produce and to copy objects with any geometries. Imitators need a lot of information to copy an object accurately. As reverse engineering has been identified as the most important information source for product imitators, AM can also help to reduce the threat of product piracy when correctly applied in the product development. Due to the layer wise production process that allows the manufacturing of very complex shapes and geometries, the reverse-engineering process can be complicated by far. By this, quite contrary to the public opinion, AM can increase the needed effort of imitators and strongly reduce the economic efficiency of product piracy. This paper will show different protection measures and a methodological approach of how to apply these measures to a product. Beside the protective effect some measures allow a traceability of parts over the product’s lifecycle and thus support the quality management of AM processes and additively produced parts.

FE-Optimization and data handling for Additive Manufacturing of structural parts - Reiher, T.; Koch, R. (26th Annual International Solid Freeform Fabrication Symposium)
Additive Manufacturing (AM) offers high potential due to its freedom of design for structural parts. Especially in combination with FE-based topology optimization an optimal use of material and thus significant weight reductions can be expected. However, the application of AM is hampered by different additional manufacturing processes along the entire production chain and data handling induced restrictions.Disadvantages emerge from a lack of adjustment of the entire design process for AM. First the optimization algorithms are not targeted to the opportunities and restrictions of AM –represented by design rules – like the design of support structures. Secondly, the CAD software is not adjusted to AM in particular. Creating freeform shaped surfaces based on the optimization results is significantly less convenient than building defined blocks or turning parts following the needs of conventional machining. The indispensable subsequent interpretation of optimization results regarding the design rules and the possibilities of CAD-tools counteracts optimal results. This paper considers different approaches for a Topology Optimization (TO)-shape regaining on different sample parts including telecommunication satellite parts. An innovative design methodology is presented getting crucial for creating high quality designs.

Sustainable Part Selection for the Use of Additive Manufacturing in Companies Focussing on Prevention of Product Piracy - Jahnke, U.; Lindemann, C. (Inside 3D Printing Conference and Expo)

Exploring the cost and lifetime benefits of a topology optimized aerospace part applying additive manufacturing - Deppe, G.; Reiher, T.; Koch, R. (International Conference Production Engineering and Management 2015)
The aerospace sector is characterized by long product life cycles and a need for lightweight design. Additive manufacturing is a technology that produces parts layer by layer and thus enables the manufacturing of any complex parts at nearly no extra costs. A topology optimization enhances the part’s performance for their special purpose. The results are often complex bionic structures that cannot be produced with conventional manufacturing technologies. The paper analyzes how the high potential of this technology can be applied to aerospace parts. A topology optimization will be conducted for an aircraft part explaining the crucial points and a life cycle analysis examines the achieved sustainable improvements for the aircraft’s life cycle.

Guidelines for a sustainable and economic selection of part candidates for space applications using additive manufacturing - Lindemann, C.; Reiher, T.; Koch, R. (Paris Space Week)

Analysis and Optimization of the Dimensional Accuracy for FDM Parts manufactured with ABS-M30 - Knoop, F.; Schöppner, Volker (ASPE Spring Topical Meeting)

Mechanical and Thermal Properties of FDM Parts manufactured with Polyamide 12 - Knoop, F.; Schöppner, Volker (26th Annual International Solid Freeform Fabrication Symposium)
Fused Deposition Modeling (FDM) is an Additive Manufacturing (AM) technology which is used for prototypes, single-part production and also small batch productions. For use as a final product, it is important that the parts have good mechanical properties, high dimensional accuracy and smooth surfaces. The knowledge of the mechanical properties is very important for the design engineer when it comes to the component design. End-use products out of the FDM process have to resist applied forces. In this paper, investigations were conducted with the polymer Polyamide 12 (FDM Nylon 12) from Stratasys Inc. This polymer can be processed with three different tip sizes resulting in different layer thicknesses from 178 µm to 330 µm. Thus, the mechanical properties were determined for these layer thicknesses and for different orientations on the build platform. In addition to the mechanical properties the thermal properties (e.g. with a DSC analysis) are also investigated.

Simulation of the Surface Topography on Laser Sintered Polymer Parts - Delfs, Patrick; Herale, A.A.; Li, Z.; Schmid, Hans-Joachim (25th Annual International Solid Freeform Fabrication Symposium)
One barrier of laser sintering (LS) to become the main process for Direct Manufacturing (DM) is the surface quality of LS parts. Hence, the property which has to be improved is the rough surfaces of LS parts due to the layered structure. Another additional effect is the incomplete melting of powder particles on the surface due to the high process temperature. In this paper we demonstrate our approach of a theoretical model for the topography of LS part surfaces. We investigated the surface roughness as a function of surface orientation. Considering that the model involves further variables as layer thickness, particle density and particle size distribution to describe the topography precisely. Experimental results were used to optimize and check the results of the model.

Three-dimensional in-process temperature measurement of laser sintered part cakes - Josupeit, Stefan; Schmid, Hans-Joachim (25th Annual International Solid Freeform Fabrication Symposium)
An uneven temperature distribution and varying cooling rates at different positions within the part cake are two of the most important challenges regarding the part quality and reproducibility of the polymer laser sintering process. In the presented work, a temperature measurement system is implemented within an EOSINT P395 laser sintering system. It allows the determination of a three dimensional temperature distribution and history during the full build and cooling process. The influence of important job parameters, for example the packing density, job height and layer thickness, can be figured out. In combination with a finite element simulation of the cooling process, the temperature measurement will be the basis for optimized process controls.

Thermal ageing of polyamide 12 used for polymer laser sintering - influence on part quality characteristics - Josupeit, Stefan; Rüsenberg, Stefan; Rupp, N.; Gessler, Monika; Schmid, Hans-Joachim (72nd Annual Technical Conference of the Society of Plastics Engineers (ANTEC 2014))
Polymer laser sintering is one of the most important additive manufacturing technologies for the tool-less production of three-dimensional prototypes and end-use parts. In this process, parts are manufactured layerwise out of a polymer powder by laser exposure. After the building process, these parts are located within a loose bulk powder cake. Due to long process times and high process temperatures, this powder ages thermally, which reduces the recyclability of the material. As a result, mixtures of used and virgin powder ("refreshed" powder) with a mixture ratio of approximately 50% are commonly used in the industry. The goal of this work is to determine the exact influence of different powder ages on resulting part quality characteristics, especially the mechanical behavior and the surface quality. Therefore, refreshed powder with different qualities adjusted by the melt volume rate (MVR) was processed along a defined process quality chain. To analyze the part qualities, mechanical tensile and profilometer tests were performed. The focus is on an application-oriented test set-up to ensure the usability of the results in the industry. The material used is polyamide 12 (PA 2200) processed on an EOSINT P395 laser sintering system from EOS GmbH, Krailling, Germany.

Development of a Basic Model to Simulate the Laser Sintering Cooling Process - Josupeit, Stefan; Ordia, L.; Schmid, Hans-Joachim (International Conference on Additive Technologies)
The process-related occurrence of varying cooling rates at different positions within the part cake is an important challenge regarding the part quality and reproducibility of the polymer laser sintering process. Temperature history dependent parameters are for example the part warpage, the crystallization behavior or powder ageing effects, which have to be considered for optimized process controls. Nevertheless, the inner temperature distribution and history during the cooling process is difficult to measure and less known yet. In this work, a Finite Element (FE) model is developed to understand and predict the temperature distribution and history within the part cake during the cooling process. Therefore, the thermal boundary conditions of a laser sintering system are analyzed and relevant parameters are identified. A basic FE model is set up in ABAQUS CAE software considering a part-free powder cake. Important thermal parameters of the bulk powder and the environment are adjusted and verified in relation to experimental in-process measured data. With this model it is possible to predict position-dependent cooling rates as a function of significant job parameters, for example the job height or the environmental conditions during the cooling phase. In combination with extended in-process temperature measurements and a consideration of built parts, this model will be an important tool for the development of optimized process controls.

Simulation of the Surface Topography on Laser Sintered Polymer Parts - Delfs, Patrick; Schmid, Hans-Joachim (25th Annual International Solid Freeform Fabrication Symposium)
One barrier of laser sintering (LS) to become the main process for Direct Manufacturing (DM) is the surface quality of LS parts. Hence, the property which has to be improved is the rough surfaces of LS parts due to the layered structure. Another additional effect is the incomplete melting of powder particles on the surface due to the high process temperature. In this paper we demonstrate our approach of a theoretical model for the topography of LS part surfaces. We investigated the surface roughness as a function of surface orientation. Considering that the model involves further variables as layer thickness, particle density and particle size distribution to describe the topography precisely. Experimental results were used to optimize and check the results of the model.

Extension of prior developed design rules (LS) - Adam, Guido; Zimmer, Detmar (ASPE - Spring topical meeting 2014)

Systematic investigations of minimum feature sizes and geometrical accuracies - Adam, Guido; Zimmer, Detmar

Design for Additive Manufacturing - Element transitions and aggregated structures - Adam, Guido; Zimmer, Detmar (CIRP Journal of Manufacturing Science and Technology)
Additive Manufacturing technologies create parts layer by layer. Thereby, lots of benefits are offered. Especially extended design freedoms provide new potentials for the design of technical parts. To make these benefits accessible to different user groups, design rules for Additive Manufacturing were developed within the project ‘‘Direct Manufacturing Design Rules’’. Therefore a process independent method was defined first. Next, design rules were developed for Laser Sintering, Laser Melting and Fused Deposition Modeling. The results were summarized in a design rule catalog and support a suitable design for Additive Manufacturing

Erweiterung des Gültigkeitsbereichs von Konstruktionsregeln beim Lasersintern - Adam, Guido